Improved Chromatographic Separation of Sitagliptin Phosphate and Metformin Hydrochloride - Hendy, Moataz S. (Int J Biomed Sci, 2015)
New UPLC method was developed for determination of sitagliptin and metformin using Symmetry C(18) column (100 mm × 2.1 mm, 2.2 μm) and isocratic elution (methanol 20%), pH (3.5) as a mobile phase. The ultraviolet detector was operated at 220 nm and the column temperature was 50°C. Linearity parameters were acceptable over the concentration ranges of 2-12 μgml(-1) and 5-35 μgml(-1) for sitagliptin and metformin, respectively. The variables were premeditated to adjust the chromatographic conditions using design of experiment. The proposed method was proved to be accurate for the quality control of the mentioned drugs in their pharmaceutical dosage form.